Brown seaweed extract enhances rooting and roots growth on Passiflora actinia Hook stem cuttings - Erik Nunes Gomes; Leandro Marcolino Vieira; Jéssica de Cássia Tomasi; Maíra Maciel Tomazzoli; Renata Lúcia Grunennvaldt; Cíntia de Moraes Fagundes; Rafaela Cristina Brunetti Machado (Ornamental Horticulture, 2018)
Passiflora actinia Hook (common name: ‘maracujá do mato’) is an important medicinal species due to significant sedative and anxiolytic activities. In order to commercially exploit the plant, however, studies on propagation to improve rooting in stem cuttings are needed. The present study was designed to evaluate the effect of the brown seaweed (Ascophyllum nodosum (L.) Le Jol.) extract when applied on P. actinia stem cuttings bases. Five concentrations of the extract in distilled water were evaluated: 0% (pure distilled water), 10%, 20%, 30% and 40%. The experimental design was completely randomized with 4 repetitions and 12 cuttings per experimental unit. Cuttings were evaluated 45 days from planting. Data were analyzed through polynomial regression analysis and Pearson’s correlation coefficients were calculated for all the variables. On average, 51.27% rooting was achieved. Rooting percentage increased linearly according to the brown seaweed extract concentrations. When compared to the control treatment, about 10% increase in rooting was observed at the treatment with 40% seaweed extract. Leaf retention response to A. nodosum increasing concentrations was also adjusted in a positive linear model. A 15.6% increase in leaf retention was observed at the 40% seaweed concentration when compared to the control. Positive correlations were observed for leaf retention and rooting percentage and leaf retention and roots length. The immersion of P. actinia stem cuttings bases in A. nodosum extract at a concentration of 40% promote positive effects on rooting and facilitate the species propagation.